PARADOKS GENDER (Kajian Feminisme Etis terhadap Kemunculan Inong Balee dalam Kekerasan Politik di Aceh) - Nugroho, Hastanti Widy; Murtiningsih, Siti (Jurnal Filsafat "WISDOM", 2008)
AbstractThis research aims to get understanding about a definition and a concept of Inong Balee in a political violence in Aceh; secondly, to get an evidence of gender paradox in the Inong Baleeâs role and existence in Aceh; thirdly, to criticize the concept of Inong Baleeâs gender paradox from Ethical Feminism viewpoint; fourthly, all of them are formulated as a recommendation for a resolution of the political violence in Aceh. The result of this research is the Inong Balee is a general term to show âa widowâ, so that the Inong Balee is not a woman groupâs name of National Liberation Front of Aceh (GAM=Gerakan Aceh Merdeka). The role of Inong Balee as mother bearing and educating children in a domestic region can make a balance with their role as a family head who must struggle in a public region to replace their husband. According to Ethical Feminism, values developed by Inong Balee actually represent the feminine values like patience, mildness, and peacefulness.Keywords: Inong Balee, gender paradox, feminism